PERAN EKSTRAKURIKULER PRAMUKA DALAM PEMBENTUKAN KARAKTER SISWA DI SMA NEGERI 1 KEDIRI TABANAN - Ni Kadek Chandra Putri Irani; I Ketut Mardika; I Nyoman Kiriana (Upadhyaya : Jurnal Penelitian Pendidikan, 2020)
The current government is incessant to deal with juvenile delinquency such as promiscuity, drugs, brawl, violence and sexual harassment that have an impact on the world of education. Along with the many problems that occur then these problems must be solved in order to achieve optimal educational goals, therefore the Government and the people of Indonesia are currently intensively implementing character education in educational institutions. At school, character education has been implemented in a way both formal and non-formal education that aims to strengthen the morale of students and shape the character of students that reflects the 18 values of the nation's character. In non-formal education, character education can be integrated through extracurricular activities. Scout education acts as a complement and supplement to formal education to add insight and improve the character of students. In SMA Negeri 1 Kediri Tabanan, non-formal educational activities or conducted outside of face-to-face lessons, one of them is scout extracurricular activities carried out by all class X (ten), both natural science majors and social science majors. In Boy Scout extracurricular activities at SMA Negeri 1 Kediri Tabanan has several activities that train physically and mentally that contribute to overcoming problems of juvenile delinquency such as camping activities, widegame activities, inauguration of scout levels and routine training in the classroom and outside the classroom. The results obtained indicate that: The implementation of Boy Scout extracurricular in Tabanan Kediri 1 High School is influenced by 2 factors namely, external factors and internal factors These two factors are the basis for Scout extracurricular activities carried out as the application of student character formation in SMA Negeri 1 Kediri Tabanan. Scout Extracurricular at SMA Negeri 1 Kediri Tabanan has carried out various innovations in its role to shape student character through innovative activity programs such as Scout Routine Training Activities in shaping responsibility characters, Scout Camp Activities in shaping independent character, Widegame Activity in shaping environmental care characters . Behind all these activities are the values of character education in the form of religious values, disciplined values, tolerance values, creative values, independent values, values of patriotism, values of social care, values of environmental care, values of achievement and responsibility.